(untitled) (Researcher: A Research Journal of Culture and Society, 2021)
The curriculum, pedagogy and assessment are the crucial interrelated elements for effective teaching learning activities in the higher education classroom. Due to so, this research project focused on analyzing the teachers and students perception on intended and enacted teaching methods in higher education teaching at Tribhuvan University. For this, the qualitative research design was applied to explore the subjective realities of research problem. It was more descriptive as well as interpretive in nature. During this process, the curriculum study, open ended questionnaire and participant observation methods were used to collect the verbal information for this interpretive inquiry. It found that both teachers and students positively perceived the six-month semester based program and expected that it would help to promote the activity based teaching learning activities. But, teachers were used to in lecturer method and more popular in higher education teaching. Beside this, the teachers were mostly practicing the lecture, demonstration through multimedia projector, question answer, self-study, project work and home assignment during the classroom instruction for professional core course curriculum.